Reviving rural recreational activities at Pulau Penarek, Muar / Nur Zahidah Mahyudin - Mahyudin, Nur Zahidah (2017)
Today, serious degradation of the rural - heritage has lead by technological development, economic and population growth and social changes in most parts of the world. These occurrences have encouraged many researchers and nature lovers to a greater appreciation of this fragile natural environment and have resulted in numerous and vary studies conducted in order to conserve it. Two methodologies had been used in this project, (i) Ian McHarg's Ecological Inventory Method and (ii) Design development for proposed strategies. This study showed that several key success factors for sustainable conservation which includes the level of the stakeholders' awareness, participation and appreciation towards heritage values and its economic potential and enforcement of legislation or policy will bring toward the successful of the rural - recreational. Indirectly, the strong genius loci and successful ecosystem can be implemented. Having shown the importance of these rural landscapes, the last sections of the study show how the present practice of environmental designers preclude the generation of ideas towards successful rural recreational activities in Pulau Penarek, Muar.